PERAN INSTRUCTIONAL LEADERSHIP DAN ADHOCRACY CULTURE TERHADAP EMPLOYEE PERFORMANCE MELALUI JOB MOTIVATION PADA GURU SDN KECAMATAN BANYUMANIK SEMARANG JUDUL ARTIKEL PENELITIAN (UKURAN HURUF 12) - Lailiyat; Asyhari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the influence of instructional leadership and adhocracy culture on employee performance, with job motivation as an intervening variable, among public elementary school teachers in the Banyumanik District. A quantitative approach was used, with data analysis conducted through the Partial Least Square (PLS) technique. The research sample consisted of 180 public elementary school teachers in the Banyumanik District, selected through purposive sampling. The results show that both instructional leadership and adhocracy culture have a positive and significant influence on job motivation. Instructional leadership also has a direct and significant effect on employee performance, while adhocracy culture does not show a significant effect on employee performance. On the other hand, job motivation serves as an intervening variable that positively and significantly affects employee performance. These findings emphasize that job motivation is a key factor in improving teacher performance, and instructional leadership plays a strategic role in fostering that motivation. Based on these results, it is recommended that school principals strengthen instructional leadership practices and that schools create a work culture that balances innovation and structure to optimally support teacher motivation and performance.